The renaissance of ordoliberalism in the 1970s and 1980s - Tim Krieger; Daniel Nientiedt (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2022)
The economic tradition of ordoliberalism, understood as the theoretical and policy ideas of the Freiburg School, emerged in 1930s and 1940s Germany. In the years thereafter, it was quickly superseded by Keynesianism and other theories imported from the English-speaking world. The crisis in Keynesian economics in the mid-1970s led to what has been described as a "renaissance of ordoliberal reasoning" (Gebhard Kirchgässner) during the late 1970s and the 1980s. The present paper describes this development in detail and shows how it affected the academic discourse and, more indirectly, policymaking. In academic economics, ordoliberal concepts were used to inform debates about pressing issues of the day such as unemployment, social security reform, competition policy, the provision of public goods, and European integration. There was, however, no consensus on the methodological question of whether ordoliberalism could be fully integrated into international research programs such as the new institutional economics or constitutional economics. The paper argues that the renaissance of ordoliberalism failed to have a lasting impact on German academic economics and discusses possible implications of this finding for the future of the ordoliberal research agenda.
Keywords: B29; D4; E6; H6; P16; 330; Ordoliberalism; Freiburg school; Economic policy; Social market economy; Keynesianism; European integration